Evaluation of the Repeatability and the Reproducibility of AL-Scan Measurements Obtained by Residents - Mehmet Kola; Hikmet Duran; Adem Turk; Suleyman Mollamehmetoglu; Ahmet Kalkisim; Hidayet Erdol (Journal of Ophthalmology)
Purpose. To assess the repeatability and reproducibility of ocular biometry and intraocular lens (IOL) power measurements obtained by ophthalmology residents using an AL-Scan device, a novel optical biometer. Methods. Two ophthalmology residents were instructed regarding the AL-Scan device. Both performed ocular biometry and IOL power measurements using AL-Scan, three times on each of 128 eyes, independently of one another. Corneal keratometry readings, horizontal iris width, central corneal thickness, anterior chamber depth, pupil size, and axial length values measured by both residents were recorded together with IOL power values calculated on the basis of four different IOL calculation formulas (SRK/T, Holladay, and HofferQ). Repeatability and reproducibility of the measurements obtained were analyzed using the intraclass correlation coefficient (ICC). Results. Repeatability (ICC, 0.872-0.999 for resident 1 versus 0.905-0.999 for resident 2) and reproducibility (ICC, 0.916-0.999) were high for all biometric measurements. Repeatability (ICC, 0.981-0.983 for resident 1 versus 0.995-0.996 for resident 2) and reproducibility were also high for all IOL power measurements (ICC, 0.996 for all). Conclusions. The AL-Scan device exhibits good repeatability and reproducibility in all biometric measurements and IOL power calculations, independent of the operator concerned.